The Impact of Diversity Inclusion Practices in the Workplace Context: The Effect of Inclusive Leadership - Silvia Platania; Claudio Maggio; Marcello Boccadamo (European Journal of Investigation in Health, Psychology and Education)
The present study explores the predictive role of organisational identification in shaping both positive and negative employee responses and the potential mediating influence of diversity climate and inclusive leadership within this relationship. Specifically, it examines how employees’ organisational identification influences their perceptions of diversity climate and inclusive leadership and how these factors, in turn, mediate their responses to organisational dissatisfaction. This study involved 307 participants from the Italian public administration who were administered a questionnaire to measure organisational identification, inclusive leadership (Inclusive Leadership Scale), the diversity climate within the organisation, and behaviours according to the EVLN model. The results indicate a direct effect of organisational identification on both the positive (Voice and Loyalty) and negative (Exit and Neglect) responses of the EVLN model. Organisational identification has a positive effect on the diversity climate. Moreover, the diversity climate mediates the relationship between organisational identification and loyalty, while inclusive leadership mediates the relationship between organisational identification and both disengagement and the willingness to address issues. These findings underscore the central role of organisational identification in shaping employees’ behavioural responses to dissatisfaction by influencing their perceptions of diversity climate and inclusive leadership. This highlights the importance of strengthening organisational identification to foster constructive behaviours and mitigate negative responses in diverse and inclusive work contexts.